Mothers' Intention for Measles-Rubella Vaccination at Bareng Primary Healthcare Center Malang - Amalia Nadya Aripuspita; Iken Nafikadini; Erwin Nur Rif'ah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2024)
Background: Measles and rubella are infectious diseases caused by viruses. The average number of measles cases found in infancy to four years old was 1.125 cases (41.8%) in 2021, with 366 and 13 cases for East Java and Malang, respectively. To eliminate measles and rubella cases in 2023, the high coverage of measles and rubella (MR) vaccination must be met at least 95%. Since 2021, the Bareng Primary Healthcare Centre in Malang has shown the lowest MR vaccination, with 217 children vaccinated (33.23%).Method: This study used a quantitative research method with observational analysis and a cross-sectional study design with a sample size of 68 people. The sampling technique used was proportionate random sampling. Then, data were done through univariate and bivariate analyses using the Spearman rank correlation test.Results: Based on the univariate results, most respondents were aged 27 to 35 years (55.9%) with secondary education (Senior High School/Vocational School/Islamic Senior High School) (55.9%) and had no income (41.2%). Based on the results of the bivariate analysis, intention and attitude correlated (0.000) with subjective norm (0.000) and perceived control over behavior (0.000). Variables significantly related to mother’s intention in giving measles-rubella vaccination were attitude over behavior, subjective norm, and perception of control over behavior. It is expected that the result of this study could raise the mother's intention to participate in counseling and socialization by providing accurate information about the MR vaccination.